Literature Review of the Transformation of Guidance and Counseling Programs in Developing the Quality of Education in Indonesia - Diana Rezu Okti; Neviyarni S; Firman; Muhammad Asyraf Che Amat (Journal Of Psychology, Counseling And Education, 2025)
Guidance and Counseling (BK) Program in Junior High Schools (SMP) has a strategic role in supporting the holistic development of students, covering academic, personal, social, and career aspects. This article aims to analyze the transformation of BK program in SMP, with a focus on the impact of program implementation and the implications of its development for the education system. Through a literature review of various recent studies and policies, this article identifies fundamental changes in the approach, methods, and objectives of BK program that are adjusted to the challenges of the modern era, such as digitalization, diversity of student needs, and increasing complexity of adolescent problems. The results of the analysis show that the transformation of BK program involves the integration of technology in counseling services, a collaborative approach between counselors, teachers, and parents, and an emphasis on the development of 21st century skills. The positive impacts of this transformation include increasing the accessibility of BK services, strengthening students' adaptability to environmental changes, and contributing to the achievement of national education goals. However, challenges remain, including the lack of counselor training related to technology, disparities in resources between schools, and the need to address the stigma against counseling services. This article emphasizes the importance of evidence-based development strategies to improve the effectiveness of BK programs in junior high schools, including strengthening counselor competencies, providing adequate infrastructure, and formulating policies that support innovation in BK services. With this approach, BK programs can play a more significant role in shaping young generations who are ready to face global challenges.